Stratification in the Early Stages of Mate Choice - Lewis, Kevin (Harvard University, 2013)
Sociologists have long studied mate choice patterns to understand the shape of stratification systems. Romantic pairing involves intimacy and trust, and is therefore a prime indicator of the extent to which members of different social groupings (race/ethnicity, social class, education, religion) accept each other as social equals. The majority of this literature focuses on marriage, given the commitment marriage implies and the availability of nationally-representative data. In this dissertation, I examine the opposite end of the relationship spectrum: The initial screening and sorting process whereby strangers consider each other as potential mates; express interest in some subset of this population but not others; and find that this interest is or is not reciprocated. This beginning stage in mate choice is particularly important for our understanding of social boundaries because personality factors are likely to matter less and social characteristics to matter more. Yet because these initial forays into relationships are typically unobserved, we know very little about whom people consider as potential mates in the first place. I ask the following questions, corresponding to three empirical chapters: First, how do individuals from different status backgrounds vary in the types of strategies that they pursue and the degree of success that they achieve? Second, what underlying dynamics of homophily, competition, and gender asymmetry give rise to observed patterns of interaction, and under what circumstances do some of these boundaries break down? Third, how do strategies as well as preferences vary at different stages of selection, and at what point is homogeneity created? To answer these questions, I use detailed longitudinal data from a popular online dating site. These data are particularly useful for the study of social inequality not only due to the unique quantity and nature of information that is available, but also because online dating has become one of the primary ways that singles meet and marry today. === Sociology